Edukasi Tuberculosis pada Masyarakat di Masa Pandemi - A.Awaliya Anwar; Devi Astuti; Era Pratiwi (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Tuberculosis is still a burden on health problems in Indonesia. And when Indonesia is also facing the Corona outbreak, this virus must be more wary of TB patients. Both of these diseases are respiratory pandemics that are transmitted through droplets. This activity aims to increase public knowledge about TB and Covid-19 related to healthy living behavior with new adaptations to prevent transmission and build public awareness to achieve successful TB treatment. The extension method provides leaflets which are distributed to participants as well as providing questionnaires before counseling (pre) and after counseling (post). the conclusion of the counseling that the results of knowledge and attitudes showed different results where for knowledge there was a difference before and after counseling while there was no difference in attitude before and after counseling